The future of events in the tourism industry: the case of the Best of the Best Things to Do 2023 on TripAdvisor - Ertas, Cagdas; Karakan, Halil Ibrahim (Emerald Group Publishing Ltd, 2024)
PurposeThis study aims to use TripAdvisor data to identify which themes and events will attract more interest in the future of tourism activities and to provide guidance to the industry accordingly.Design/methodology/approachThis study used qualitative case study approach. To identify key themes in the top-rated activities, thematic analysis of user-generated content was conducted through MAXQDA 2020 Analytics Pro software.FindingsThe findings of this study indicate a growing trend in tourist preferences, with a notable increase in the popularity of wellness activities such as spa treatments and yoga retreats. Tourists also highly prefer cultural experiences like local festivals and historical tours, adventure activities such as hiking and water sports, and food-related activities like cooking classes and wine tastings. There is a significant trend towards sustainable and environmentally friendly tourism activities. These results underscore the need to cater to diverse tourist interests in developing future tourism offerings.Practical implicationsDeveloping innovative events, using data-driven marketing strategies, involving local communities, and catering to diverse preferences can enhance the sustainability and competitiveness of the tourism sector.Social implicationsUnderstanding tourists' tendencies towards cultural, adventurous and sustainable experiences helps tourism operators and managers to create offers that satisfy tourists while promoting environmentally friendly practices. This shift promotes cultural preservation, environmental protection and community involvement.Originality/valueThis study uniquely analyzes top-rated TripAdvisor activities to identify key trends in tourist preferences, highlighting the growing demand for cultural, adventurous, gastronomic, and sustainable tourism.
Keywords: Event tourism; Tourist preferences; Sustainability; TripAdvisor